Digital Literacy and Learning Interaction: An Ethnographic Study of Indonesian EFL Classrooms - Adi F. Mahmud; Murni Mahmud; Sukardi Weda; Munir Munir (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This ethnographic study examines the relationships between digital literacy and learning interactions in Indonesian EFL classes. The study seeks to elucidate the role of digital tools in mediating educational practices and interactional dynamics between educators and learners. Data were collected over six months at SMA Negeri Ternate, Indonesia, using participant observation, semi-structured interviews, document analysis, and field notes, involving five teachers and ten students. The findings suggest a triadic interactional framework, comprising learner-content, learner-instructor, and learner-learner interactions, all of which are shaped by digital integration. Students utilized multimedia resources such as YouTube and ChatGPT, promoting independence and multimodal understanding. Nonetheless, conventional assumptions of teacher authority persisted, and digital disparities frequently limited peer participation. Three cultural elements emerged: technology-enhanced instruction, enduring teacher authority, and flexible peer solidarity. The study concludes that digital literacy alters classroom dynamics, but it must be grounded in local educational and cultural norms. It necessitates culturally responsive instructional design and fair access to improve engagement and maximize the educational potential of digital literacy.